Induction of mild hypothermia in cardiac arrest survivors presenting with cardiogenic shock syndrome - Škulec, Roman; Kovárník, Tomáš; Dostálová, Gabriela; Kolář, Jiří; Linhart, Aleš (Acta anaesthesiologica Scandinavica, 2008)
BACKGROUND: Induction of mild hypothermia (MH) in patients resuscitated from cardiac arrest improves their outcome. However, benefits and risks of MH in patients who remain in cardiogenic shock after the return of spontaneous circulation (ROSC) are unclear. We analysed all cardiac arrest survivors who were treated with MH in our intensive coronary care unit (CCU) and compared the outcome of patients with cardiogenic shock syndrome (CSS) with those who were circulatory stable. METHODS: We performed retrospective analysis of all consecutive cardiac arrest survivors treated by MH in our CCU from November 2002 to August 2006. They were classified into two groups, according to whether they met the criteria for cardiogenic shock or not before MH initiation. RESULTS: Out of 56 consecutive patients, 28 fulfilled criteria of cardiogenic shock before MH initiation (group A) and 28 were relatively stable (group B). In-hospital mortality was 57.1% in group A and 21.4% in group B patients (P=0.013). Favourable neurological outcome anytime during hospitalization was found in 67.9% of group A patients and in 82.1% of group B subjects (P=0.355). Favourable discharge neurological outcome was reached in 39.3% in group A and in 71.4% in group B (P=0.031). The complication rate in both groups did not differ. CONCLUSION: While in-hospital mortality in cardiac arrest survivors treated by MH was expectably higher in those with cardiogenic shock than in stable patients, the favourable neurological outcome during hospitalization was comparable in both groups. Therefore, induction of MH should be considered in cardiac arrest survivors with CSS after ROSC.
Keywords: odds ratio; hodnocení rizik; Female; Hypothermia, Induced; Age Factors; výsledek terapie; ženské pohlaví; mortalita v nemocnicích; Outcome and Process Assessment, Health Care; věkové faktory; lidé; Neurologic Examination; Survival Analysis; Heart Arrest; terapeutická hypotermie; Treatment Outcome; neurologické vyšetření; Risk Assessment; krevní tlak; srdeční frekvence; Middle Aged; Risk Factors; retrospektivní studie; Coronary Care Units; koronární jednotky; Male; Aged; Czech Republic; srdeční zástava; Shock, Cardiogenic; rizikové faktory; analýza přežití; Česká republika; Hospital Mortality; Syndrome; lidé středního věku; kardiogenní šok; senioři; mužské pohlaví; výsledky a postupy - zhodnocení (zdravotní péče); Blood Pressure; Retrospective Studies; Heart Rate; Odds Ratio; syndrom; Humans